2008
DOI: 10.1029/2007jg000415
|View full text |Cite
|
Sign up to set email alerts
|

A dynamic model of oceanic sulfur (DMOS) applied to the Sargasso Sea: Simulating the dimethylsulfide (DMS) summer paradox

Abstract: [1] A new one-dimensional model of DMSP/DMS dynamics (DMOS) is developed and applied to the Sargasso Sea in order to explain what drives the observed dimethylsulfide (DMS) summer paradox: a summer DMS concentration maximum concurrent with a minimum in the biomass of phytoplankton, the producers of the DMS precursor dimethylsulfoniopropionate (DMSP). Several mechanisms have been postulated to explain this mismatch: a succession in phytoplankton species composition towards higher relative abundances of DMSP prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 95 publications
(249 reference statements)
4
74
0
Order By: Relevance
“…In polar regions on the other hand, a coupling between phytoplankton biomass and DMS does exist (Kettle et al 1999). Overall, it appears that surfacewater DMS concentration correlates much better with incident solar irradiance than with carbon biomass (Vallina and Simo 2007), and the question is which processes are responsible for this correlation.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In polar regions on the other hand, a coupling between phytoplankton biomass and DMS does exist (Kettle et al 1999). Overall, it appears that surfacewater DMS concentration correlates much better with incident solar irradiance than with carbon biomass (Vallina and Simo 2007), and the question is which processes are responsible for this correlation.…”
Section: Introductionmentioning
confidence: 87%
“…In a recent model exercise applied to the Sargasso Sea, the light-induced S:N ratio of phytoplankton, which in the model is a measure for a shift in species composition or physiological adaptation of the DMSP production, and light-induced DMS exudation by DMSP-producing algae were among the crucial processes to reliably predict the DMS summer paradox (Vallina et al 2008). In a sensitivity analyses in which parameters were increased or decreased by 50%, these two processes resulted in 100% change of the annual DMS budget.…”
Section: Introductionmentioning
confidence: 99%
“…Marlon et al, 2008); and iii) some ecosystems, such as savannas, are essentially fire-regulated systems and would burn regularly irrespective of anthropogenic pressures. However, these are generalizations, and it is likely that in many regions wildfires occur because of a mix of natural and anthropogenic factors (van der Werf et al, 2008). This should be kept in mind when discussing possible climate feedbacks involving wildfires as these feedbacks could be different in the absence or presence of anthropogenic factors.…”
Section: Feedback Processes Involving Wildfiresmentioning
confidence: 99%
“…Penner et al (2001) reported global emissions of organic matter of 45-80 Tg a −1 and of black carbon (BC) of 5-9 Tg a −1 for biomass burning (including biofuels). More recent inventories of large-scale (or open) burning rely on remote sensing estimates of fire counts (Generoso et al, 2003) or area burned (Hoelzemann et al, 2004;van der Werf et al, 2004). The range of estimates for annual emissions of particulate organic matter from wildfires is 20 to 35 Tg a −1 (see Fig.…”
Section: The Impact Of Wildfires On Aerosol and Climatementioning
confidence: 99%
“…UVR doses) and may be the major driver of the DMS summer-paradox. [16] Is oceanic DMS a globally relevant source of cloud condensation nuclei?…”
Section: What Is the Climatic Factor That Drives Oceanic Dms Productimentioning
confidence: 99%